METODE RASIO SEBAGAI TOOL’S KINERJA KEUANGAN PT BANK SYARIAH MANDIRI - Muhlis, Muhlis (Universitas Muhammadiyah Makassar, 2021)
A quality bank is able to meet its financial performance weight ratio, as a form of achievement within a certain period of time. This paper uses the financial ratio method with the financial statement data of PT Bank Syariah Mandiri. The purpose of this paper is to dissect financial statement items, look for relationships between components in financial statements so that the information can be used in making company decisions. The results of the paper show that the state of the performance of PT Bank Syariah Mandiri based on the 2014-2016 financial reports is in quite good condition. The financial ratios show, among others, the liquidity ratio of current assets (current ratio) shows a value of 7.75, which means that 1 rupiah of current debt is secured by Rp.7.75 rupiah of current assets, the previous year which was Rp.6.84 and Rp.6.80, -. Then the solvency ratio shows that the long-term liabilities are quite solvable. This situation can be seen from the Debt to Total Asset Ratio which is always below 50% from 2014-2016. The results of the profitability analysis also always experience developments from year to year.Keyword: Annualt Report, Ratio Analysis, Financial Peformance